2014
DOI: 10.3390/ijms150813482
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Atopy: Role in Atopic Dermatitis and Asthma

Abstract: Melatonin may have important immunostimulatory actions in allergic diseases, in addition to its well-known antioxidant and cytoprotective effects in several inflammatory conditions. The activation of the immune system leads to free radical production associated with decreased melatonin levels and depressed antioxidant enzyme activities in several inflammatory diseases. Many skin disorders, including atopic dermatitis, are accompanied by infiltration and activation of mast cells, which release vasoactive and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 85 publications
0
70
0
3
Order By: Relevance
“…As mast cells are highly sensitive to pathogen exposure, this could be an explanation for the divergent results. Other environmental influences like sleep cycles and different diet could as well influence mast cell quantities (, S3–S5 in Data S1). Although we performed our experiments with the exact same mouse strain as Zhou et al, the two manuscripts differ as we only used corresponding littermates as WT controls instead of unrelated C57BL/6 mice.…”
Section: Resultsmentioning
confidence: 99%
“…As mast cells are highly sensitive to pathogen exposure, this could be an explanation for the divergent results. Other environmental influences like sleep cycles and different diet could as well influence mast cell quantities (, S3–S5 in Data S1). Although we performed our experiments with the exact same mouse strain as Zhou et al, the two manuscripts differ as we only used corresponding littermates as WT controls instead of unrelated C57BL/6 mice.…”
Section: Resultsmentioning
confidence: 99%
“…Although thyroid autoimmunity has regularly been associated with atopy in children, the possible protective role of antioxidants, such as melatonin, has not yet been fully investigated, although its role has been documented in other atopic conditions, such as dermatitis and asthma [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…Experimental data [17] suggested that melatonin inhibits development of atopic eczema, a condition accompanied by infiltration and activation of mast cells with release vasoactive and proinflammatory mediators, and reduces serum total IgE and IL-4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although extensive experimental and human studies have been performed to identify the immunological cause of atopy, its etiology remains obscure [2,3,4,5,6]. …”
Section: Introductionmentioning
confidence: 99%